2007
DOI: 10.2147/tcrm.2007.3.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Darbepoetin alpha in the treatment of cancer chemotherapy-induced anemia

Abstract: Anemia is a common, but underestimated and undertreated, complication of patients with cancer receiving chemo-or radiotherapy, and negatively affects their quality of life (QoL). Erythropoietic proteins (EPS) offer an effective treatment of cancer anemia and ameliorate QoL, although their use requires the correct targeting of hemoglobin increase to avoid thromboembolic complications. Currently the effort is focused on offering patients this effective treatment with reduced frequency of administration. Higher w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…According to a logistic regression analysis, patients who received docetaxel developed anemia at a higher rate than those who did not receive docetaxel ( Table 3 ). Correspondingly, similar findings indicated a significant relationship between docetaxel and anemia [ 35 ]. Despite the fact that anthracycline and taxane-based chemotherapeutic regimens have become the standard of care for breast cancer treatment, they have been shown to reduce mortality and improve survival rates.…”
Section: Discussionmentioning
confidence: 65%
“…According to a logistic regression analysis, patients who received docetaxel developed anemia at a higher rate than those who did not receive docetaxel ( Table 3 ). Correspondingly, similar findings indicated a significant relationship between docetaxel and anemia [ 35 ]. Despite the fact that anthracycline and taxane-based chemotherapeutic regimens have become the standard of care for breast cancer treatment, they have been shown to reduce mortality and improve survival rates.…”
Section: Discussionmentioning
confidence: 65%
“…The above observation helped to strengthen our earlier report that Chemotherapy had greatest impact on Hb level during therapy. This assertion was supported by three different studies elsewhere Ludwig et al, Grossi et al and Jassen et al which showed that Chemotherapy is a well-known bone marrow depressant and acute cytotoxic agent [3,27,28], To reduce a lot of confounding factors which will likely influence the results of this study, patients that had World Health Organization (WHO), performance status of 0 and 1 were selected. Out of 201 patients studied, 54% (108) had WHO performance status of 0 while 46% (93) had WHO performance status of 1.…”
Section: Discussionmentioning
confidence: 52%
“…According to a logistic regression analysis, patients who received docetaxel developed anemia at a higher rate than those who did not receive docetaxel (Table 3). Correspondingly, similar ndings indicated a signi cant relationship between doceatxel and anaemia (35). Despite the fact that anthracycline and taxane-based chemotherapeutic regimens have become the standard of care for breast cancer treatment, they have been shown to reduce mortality and improve survival rates.…”
Section: Discussionmentioning
confidence: 77%